Forehead reflectance photoplethysmography to monitor heart rate: preliminary results from neonatal patients - Grubb, Mark; Carpenter, James; Crowe, John A.; Teoh, Jeremy; Marlow, Neil; Ward, Carole; Mann, Chantelle; Sharkey, Don; Hayes-Gill, Barrie R. (Institute of Physics, 2014)
Around 5%–10% of newborn babies require some form of resuscitation at birth and heart rate (HR) is the best guide of efficacy. We report the development and first trial of a device that continuously monitors neonatal HR, with a view to deployment in the delivery room to guide newborn resuscitation. The device uses forehead reflectance photoplethysmography (PPG) with modulated light and lock-in detection. Forehead fixation has numerous advantages including ease of sensor placement, whilst perfusion at the forehead is better maintained in comparison to the extremities. Green light (525 nm) was used, in preference to the more usual red or infrared wavelengths, to optimize the amplitude of the pulsatile signal. Experimental results are presented showing simultaneous PPG and electrocardiogram (ECG) HRs from babies (n = 77), gestational age 26–42 weeks, on a neonatal intensive care unit. In babies ≥32 weeks gestation, the median reliability was 97.7% at ±10 bpm and the limits of agreement (LOA) between PPG and ECG were +8.39 bpm and −8.39 bpm. In babies <32 weeks gestation, the median reliability was 94.8% at ±10 bpm and the LOA were +11.53 bpm and −12.01 bpm. Clinical evaluation during newborn deliveries is now underway.